Protection of mobile and wireless networks against service availability attacks - Gines Escudero-Andreu (2018)
Cellular and wireless communications are widely used as preferred technology for accessing network services due to their flexibility and cost-effective deployment. 4G (4th Generation) networks have been gradually substituting legacy systems, relying on the existing commercial and private Wireless Local Area Network (WLAN) infrastructures, mainly based on the IEEE 802.11 standard, to provide mobile data offloading and reduce congestion on the valuable limited spectrum. Such predominant position on the market makes cellular and wireless communications a profitable target for malicious users and hackers, justifying the constant effort on protecting them from existing and future security threats. [Continues.]